Explaining right and wrong - Ferrari, G; Geoffrey Harrison Ferrari (2008)
When an act is right or wrong, there may be an explanation why. Different moral theories recognize different moral facts and offer different explanations of them, but they offer no account of moral explanation itself. What, then, is its nature? This thesis seeks a systematic account of moral explanation within a framework of moral realism. In Chapter 1, I develop a pluralist theory of explanation. I argue that there is a prima facie distinctive normative mode of explanation that is essential to moral theory. In Chapter 2, I characterize normative explanation through its formal properties. I then draw on John Mackie’s claim that moral explanations are queer to develop a powerful form of moral scepticism. In Chapters 3–4, I reject attempts to reduce normative explanation to logical necessity, metaphysical necessity, or conceptual (analytic) necessity. The failure of these accounts is taken to reinforce Mackie’s scepticism. In Chapter 5, I defend a partial analysis of normative explanation in terms of irreducible normative laws. I argue that irreducible normative laws offer a realist, though non-naturalist, answer to Mackie’s scepticism. The existence of irreducible normative laws then is defended as offering the best realist explanation of why rightness and wrongness supervene on descriptive properties. In Appendix A, I discuss the claim the normative explanation has an essential connection to the motivation of virtuous agents. I defend this claim from certain difficulties posed by Jonathan Dancy’s recent work.